2014
DOI: 10.1097/adt.0b013e31827914b3
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Treatment Initiation Among Individuals With Serious Mental Illness and Substance Abuse Disorder

Abstract: Introduction:Studies have shown that approximately half of individuals with mental health disorders have a comorbid drug and alcohol diagnosis. Enrolling dually diagnosed patients in outpatient treatment programs has been a unique challenge for decades. Research identifying factors associated with patient treatment initiation has been limited. Clinicians have suspected that certain drugs, such as methamphetamine, may be a deterrent to treatment initiation. We wanted to identify factors that might be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…), factors that affect treatment initiation (McClean et al . ), and predictors of change (Bennett et al . ) and aftercare treatment adherence (Pantalon et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), factors that affect treatment initiation (McClean et al . ), and predictors of change (Bennett et al . ) and aftercare treatment adherence (Pantalon et al .…”
Section: Introductionmentioning
confidence: 99%
“…We found a few studies that focussed on patients with a dual diagnosis in outpatient settings. These studies were quantitative, describing the benefits of shifting the locus of acute treatment from hospital to community care (Timko et al 2006), factors that affect treatment initiation (McClean et al 2013), and predictors of change (Bennett et al 2012) and aftercare treatment adherence (Pantalon et al 2014). None of them focussed on nurse-patient interactions or conversations.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies, with more precise methodological design, are warranted to provide evidence whether structured, more intensive, and community-based residential treatment forms that facilitate twelve-step involvement can contribute to beneficial outcomes among AUD patients with more severe psychopathological symptomatic profiles ( Karriker-Jaffe, Klinger, Witbrodt, & Kaskutas, 2018 ). Previous studies have suggested that integrated treatment forms, which simultaneously address AUD-related and psychological-related impairments might have beneficial effects among patients with comorbid AUD and psychiatric disorders ( McClean, Anspikian, Winters, & Tsuang, 2014 ). Interventions which combined treatment approaches focusing on AUD and co-occurring psychiatric disorders were used to facilitate simultaneous improvements in symptomatology of AUD as well as comorbid disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, with more precise methodological design, are warranted to provide evidence whether structured, more intensive, and community-based residential treatment forms that facilitate twelve-step involvement can contribute to beneficial outcomes among AUD patients with more severe psychopathological symptomatic profiles (Karriker-Jaffe et al, 2018). Previous studies have suggested that integrated treatment forms, which simultaneously address AUD-related and psychological-related impairments might have beneficial effects among patients with comorbid AUD and psychiatric disorders (McClean et al, 2014). Interventions which combined treatment approaches focusing on AUD and co-occurring psychiatric disorders were used to facilitate simultaneous improvements in symptomatology of AUD as well as comorbid disorders.…”
Section: V/6 Conclusionmentioning
confidence: 99%